2019
DOI: 10.1101/19003327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alcohol use and cognitive functioning in young adults: improving causal inference

Abstract: Background and Aims: There have been few longitudinal studies of association between alcohol use and cognitive functioning in young people. We aimed to examine whether alcohol use is a causal risk factor for deficient cognitive functioning in young adults. Design: Linear regression was used to examine the relationship between longitudinal latent class patterns of binge drinking and subsequent cognitive functioning. Two-sample Mendelian randomisation (MR) tested evidence for the causal relationship between alco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It would be useful to investigate this further, potentially with Mendelian randomisation type or genomic structural equation modelling (Grotzinger et al, 2019) approaches, but the current GWAS for emotion recognition are underpowered to do this. We were also unable to examine the association between emotion recognition polygenic risk scores and autistic traits due to sample overlap with the GWAS for the DANVA (Coleman et al, 2017) and ERT (Mahedy et al, 2019) also being conducted in ALSPAC. To investigate whether our findings could be a result of shared genetic aetiology we looked at genetic correlations between these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to investigate this further, potentially with Mendelian randomisation type or genomic structural equation modelling (Grotzinger et al, 2019) approaches, but the current GWAS for emotion recognition are underpowered to do this. We were also unable to examine the association between emotion recognition polygenic risk scores and autistic traits due to sample overlap with the GWAS for the DANVA (Coleman et al, 2017) and ERT (Mahedy et al, 2019) also being conducted in ALSPAC. To investigate whether our findings could be a result of shared genetic aetiology we looked at genetic correlations between these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The GWAS listed in Table 1 were used to identify genetic variants (Single Nucleotide Polymorphisms; SNPs) associated with inflammation (CRP, IL-6, sIL6R and GlycA) and cognition (working memory, emotion recognition, response inhibition) (Ahluwalia et al, 2021; Han et al, 2020; Kettunen et al, 2016; Ligthart et al, 2018; Mahedy et al, 2021; Rosa et al, 2019; Sarwar et al, 2012; Swerdlow et al, 2012). For details on GWAS (including any overlap with ALSPAC) and accessing data, see Supplementary Tables S8 and S10.…”
Section: Methodsmentioning
confidence: 99%
“…First, abundant evidence shows that patients with a diagnosis of alcohol use disorder exhibit deficits on a range of executive tasks [11]. Second, among adolescents and students, heavy social drinking or binge-drinking is typically not found to result in poorer executive functioning [12]- [16]. It has been suggested that compensatory mechanisms may dissipate negative effects of repeated alcohol intoxication on the developing brain [17], or that detrimental effects may appear at later age as a result of cumulative exposure [18].…”
Section: P R E -P R I N T Introductionmentioning
confidence: 99%